Formation of regional competitive advantages in the context of territorial and digital marketing - Nikulnikova, Hanna; Astafieva, Kateryna; Astafiev, Oleksandr (Management and Entrepreneurship: Trends of Development, 2026)
The article explores the formation of competitive advantages of regions within the conditions of economic transformation and the growing influence of digital technologies. It emphasizes that regional competitiveness is increasingly determined not only by traditional resource factors but also by the capacity of territories to design, position, and communicate a coherent value proposition to diverse stakeholder groups. In this context, marketing-oriented governance emerges as a strategic component of regional development. The purpose of the research is to substantiate the theoretical and methodological foundations of integrating territorial and digital marketing as complementary instruments for strengthening regional competitiveness. The subject of the study encompasses the mechanisms, strategic effects, and management implications associated with the application of marketing approaches in regional policy. The methodological framework is based on comparative analysis, structural-functional decomposition, and the synthesis of interdisciplinary concepts derived from regional economics, marketing, and digital transformation studies. Systemic analysis is applied to identify interdependencies between territorial branding, digital communication channels, stakeholder perception, and socio-economic outcomes. The findings indicate that sustainable regional competitive advantages depend on the strategic alignment of territorial identity with digital interaction environments. The integration of territorial and digital marketing produces synergy effects reflected in reputational strengthening, enhanced investment attractiveness, and deeper stakeholder engagement. Simultaneously, the study reveals that institutional, organizational, and coordination constraints reduce the effectiveness of fragmented marketing initiatives. The originality and value of the research consist in the development of an integrative conceptual framework explaining the combined impact of territorial and digital marketing on regional competitiveness. Practical implications relate to the formulation of coordinated regional policies prioritizing governance coherence, digital analytics, and long-term brand management. The conceptual orientation of the study defines its limitations and suggests directions for future empirical validation.JEL Classification: R11, M31, L86, O33.